Study on nanomechanical properties of 4H-SiC and 6H-SiC by molecular dynamics simulations. Issue 17 (1st December 2019) - Tian, Zige; Xu, Xipeng; Jiang, Feng; Lu, Jing; Luo, Qiufa; Lin, Jiaming
Abstract: This article aimed to study the nanomechanical properties of silicon carbide under nanoindentation and nanoscratching by the molecular dynamics (MD). First, the MD models were established and experimentally verified. Then, the MD results were used to analyze the subsurface morphology and crystal defects occurring during the processes, which are comparatively difficult to study through experiments. For comparison, the C face and the Si face of 4H-SiC and 6H-SiC were selected for research. The results indicate that 4H-SiC shows greater normal resistance than 6H-SiC for both faces, and the C face may be easier to machine than the Si face for both 4H- and 6H-SiC. In addition, the hexagon amorphous patterns were found in the horizontal cross-sections views after the indentation, which were deemed to make up of two mutually central symmetric triangles. The results show that these amorphous patterns may be caused by the slip systems of 4H-SiC and 6H-SiC, which are mainly take place on the (0001) basal plane and along the <11–20> directions, depending on their special lattice structures. Through MD simulations, the formation mechanism of sub-surface damage of SiC substrates is much clearer.